The Israeli Radio-play: Towards a Socio-thematic Analysis - Levy, Shimon (MiKAN, 2006)
This article presents an outline for a socio-thematic analysis of 40years of radio-plays in Hebrew. The examined corpus comprises1850 works, some of which are originally radiophonic and othersadaptations from other media, broadcast by the Israeli radio-dramadepartment between 1954 to 1992. Although clearly influencedby European radio-drama, Israeli radio-plays have developedtheir own unique blend of "form and content". Through a selectednumber of radio-plays, this first-of-its-kind survey offers athematic approach to the repertoire, in dealing with topics suchas the Holocaust, the Arab-Israeli conflict, and the image of theIsraeli-born "Sabra".